3.THE COMPARISON BETWEEN THE EFFECT OF TWO HOURS ATROPINIZATION VERSUS THREE DAYS ATROPINIZATION ON THE CYCLOPLEGIC OUTCOME IN CHILDREN (Iraqi Journal of Medical Sciences, 2019)
Background: Cycloplegia abolishes the accommodative power by causing paralysis of ciliary muscle by anticholinergic drugs, which will inhibit stimulation of both ciliary muscle and sphincter pupillae causing cycloplegia and mydriasis. Atropine is widely used in cycloplegic refraction despite its potential toxicity.Objective:To evaluate the possible role of two hours atropinization versus three days atropinization on the cycloplegic outcome in children.Methods: This is a clinical interventional study that included fifty children aged two to seven years' old who attended Ibn Alhaitham Teaching Hospital from October 2012 to March 2013; manual refraction was done for each child after 120 minutes of two drops atropine 1% five minutes apart and refraction was repeated after three days of twice daily atropine 1% administration by the parents. T-test was used for means comparison.Results: Fifty patients (26 males, mean age 3.89 ± 1.3) were included in the study. Spherical equivalent results obtained after three days atropinization (M = 4.2, SD = 1.85) were significantly higher than those obtained after two hours atropinization (M = 3.84, SD = 1.64) (t(49) = - 6.60, p < 0.05).Conclusion: Two hour atropinization was inferior to the standard three days atropinization as it has less cycloplegic effect and so it cannot be recommended based on the current evidence.Keywords: Atropine, cycloplegia, atropinization, refraction Citation: Mohamad AA, Mahdi HA, Younis MS. The comparison between the effect of two hours atropinization versus three days atropinization on the cycloplegic outcome in children. Iraqi JMS. 2018; 16(4): 372-377. doi: 10.22578/IJMS.16.4.3
Keywords: Atropine; cycloplegia; atropinization; refraction